Male-female comparison of vasomotor effects of circulating hormones in human intracranial arteries - Jacob C. A. Edvinsson; Irena Grubor; Aida Maddahi; Lars Edvinsson (The Journal of Headache and Pain, 2024)
Abstract Background The purpose of this study was to examine whether there are sex differences in vasomotor responses and receptor localization of hormones and neuropeptides with relevance to migraine (vasopressin, oxytocin, estrogen, progesterone, testosterone, amylin, adrenomedullin and calcitonin gene-related peptide (CGRP)) in human intracranial arteries. Methods Human cortical cerebral and middle meningeal arteries were used in this study. The tissues were removed in conjunction with neurosurgery and donated with consent. Vasomotor responses of arteries, after exposure to hormones or neuropeptides, were recorded using a wire myograph. Immunohistochemistry was performed to examine the expression and localization of their receptors within human intracranial arteries. Results Vasopressin showed the strongest contractile responses, followed by oxytocin and progesterone. CGRP displayed the strongest vasodilatory response when compared to adrenomedullin, amylin, testosterone and estrogen. No significant differences were observed in vasomotor responses between male and female arteries. The vasomotor effects were supported by the presence of corresponding receptors in the vascular smooth muscle cells. Estrogen receptors (ERα and ERβ), progesterone receptor (PR), vasopressin 1a receptor (V1aR), and the oxytocin receptor (OTR) were expressed in the walls of both cerebral arteries overlying the cerebral cortex and intracranial arteries of the dura mater. ERα, V1aR, and PR were found to be localized in both smooth muscle cells and endothelium, whereas OTR was exclusively located within the smooth muscle cells. Conclusions Hypothalamic, sex hormones and the pancreas hormone (amylin) receptors are expressed in the human intracranial artery walls. The vasomotor responses revealed no sex differences, however contractile responses to vasopressin was higher and more potent in MMA compared to CCA when pooling data from both sexes. Overall, the hormones estrogen, progesterone and oxytocin, which drop in circulating levels at onset of menstruation, only showed modest vasomotor responses as compared to CGRP. This suggests that their role in inducing menstrual migraine attacks is not directly related to vasomotor responses. Graphical Abstract